Dynamic Capabilities, Technological Capability, and Green Innovation Performance in Indonesian Manufacturing Industries - Halek Mu’min; Thomas Stefanus Kaihatu; Denny Bernardus (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Manufacturing industries face increasing pressure to adopt green innovation to balance environmental sustainability and competitive performance, particularly in developing economies like Indonesia. This study investigates how dynamic capabilities, influenced by market dynamics and moderated by technological capabilities, green innovation performance in Indonesian manufacturing firms. The research aims to examine the relationships among these variables and their impact on sustainable outcomes. A cross-sectional, multi-informant survey was conducted with 250 manufacturing firms in Indonesia, using validated scales to measure market dynamics, dynamic capabilities, technological capabilities, and green innovation performance. Data were analyzed using Partial Least Squares Structural Equation Modelling. The findings confirm that dynamic capabilities and technological capabilities significantly enhance green innovation performance, with market dynamics acting as a strong antecedent to dynamic capabilities. However, the moderating effect of technological capabilities is weak, likely due to Indonesia’s infrastructural and regulatory constraints. This study concludes that Indonesian manufacturing firms can improve green innovation by strengthening dynamic capabilities and investing in technological infrastructure, despite local challenges. These findings offer insights for managers and policymakers to foster sustainable practices in developing economies.